WRITING SKILL AT FIFTH SEMESTER THE ARGUMENTATIVE ESSAY: THE ANALYSIS - MAS DARUL IHSAN (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2017)
Become one of the English skill in which needs the intention or behavioral dimension habit and ability for those who always drill theirself to regularly write, writing skill need to be taught and learned intensively in the colleagues and universities. Consequentely, writing skill become one of the compulsory subject in the English Department, Especially the Faculty of Teacher Training and Education in Muhammadiyah University of Sidoarjo. Ornamentally crafted with Academic Writing subject at the fifth semester, the curriculum says that students proposed to be able to write argumentative essay. To analyze the students skill of argumentative essay, the qualitative research is made by using the theory from Oshima and Hogue (2006). The results show that: 1)the crtical thinking of making the argumetative essay from the students are that the students are able to stand up on a side of the student’s point of view and make sure the reader (s) that the student’s arguments are right, it is supported by solid reason and solid evidence. 2) the students are able to make make sure the reader (s) that the student’s arguments are right, it is supported by solid reason but with weak evidence, and some grammatical error. Last 3) that the students are able to make make sure the reader (s) that the student’s arguments are right, but it is not supported by solid reason and solid evidence. Key words: argumentative essay, block pattern, point by point pattern.